DIFFERENCES IN STOCK PERFORMANCE OF THE SRI-KEHATI AND LQ45 INDEX THROUGH RISK-ADJUSTED RETURN METHOD - Lousius, Pamela Angelica; Ekadjaja, Margarita (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to examine differences in stock performance between the SRI-KEHATI and LQ45 indices using the risk adjusted return method through the Sharpe, Treynor and Jensen ratios. Testing was carried out from 2020 to 2022 on fifteen SRI-KEHATI index shares and fifteen LQ45 shares using the Mann-Whitney test, Independent Sample t Test, and Kruskal-Wallis test. The research results show that there are no differences in stock performance in the two indices using the Sharpe method, Treynor and Jensen methods. It was also found that there were differences between the three methods in the SRI-KEHATI and LQ45 indexes, where the Treynor method was the most consistent method in measuring the performance of the two indices. Overall, the LQ45 index is superior based on average stock performance, especially in the 2020 and 2021 periods, so it can outperform the increase in the SRI-KEHATI index in 2022.